Characteristics that make the Fallopia genus (Polygonaceae) highly invasive - Sołtysiak, Justyna; Brej, Teresa (Ecological Questions, 2012)
Representatives of the Fallopia genus: Fallopia japonica, Fallopia sachalinensis and Fallopia × bohemica are known as successful invaders, wide spread throughout Europe and North America. This paper focuses on the invasive Fallopia complex and presents some features (a wide ecological amplitude, high competition abilities, sexual reproduction by hybridization) responsible for the fact that all species of the Fallopia genus are aggressive and noxious invaders.